Minimum acceptable diet feeding practice and associated factors among children aged 6-23 months in east Africa: a multilevel binary logistic regression analysis of 2008-2018 demographic health survey data - Misganaw Gebrie Worku; Tesfa Sewunet Alamneh; Getayeneh Antehunegn Tesema; Adugnaw Zeleke Alem; Zemenu Tadesse Tessema; Alemneh Mekuriaw Liyew; Yigizie Yeshaw; Achamyeleh Birhanu Teshale (BMC, 2022)
Abstract Background Despite the proportion of receiving a minimum acceptable diet (minimum meal frequency and minimum dietary diversity) is lower in east Africa, there is limited evidence on minimum acceptable diet. Therefore, this study aimed to investigate the minimum acceptable diet and associated factors among children aged 6-23 months in east Africa. Methods A secondary data analysis of the most recent Demographic and Health Survey (DHS) data of 12 east African countries was done. A total weighted sample of 34, 097 children aged 6-23 months were included. A multilevel binary logistic regression model was applied. The Intra-class Correlation Coefficient (ICC) and Median Odds Ratio (MOR) were calculated to assess the clustering effect. Besides, deviance was used for model comparison as the models are nested models. Both crude and adjusted Odds Ratio (OR) with a 95% Confidence Interval (CI) were reported as potential predictors of minimum acceptable diet feeding practice. Results The prevalence of minimum acceptable diet feeding practice among children in east Africa was 11.56%; [95%CI; 11.22%, 11.90%]. In the multilevel analysis; child age of 12-17 month (AOR = 1.33: 95%CI; 1.20, 1.48), maternal primary (AOR = 1.21: 95%CI; 1.08, 1.35), secondary (AOR = 1.63: 95%CI; 1.44, 1.86) higher (AOR = 2.97: 95%CI; 2.30, 3.38) education level, media exposure (AOR = 1.38, 95%CI; 1.26, 1.51), household wealth statues (AOR = 1.28, 95%CI; 1.15, 1.42 for middle and AOR = 1.50: 95%CI; 1.42, 1.71 foe rich), employed mother (AOR = 1.27: 95%CI; 1.17, 1.37), maternal age 25-34 (AOR = 1.20: 95%CI; 1.09, 1.32) and 35-49 (AOR = 1.22: 95%; 1.06, 1.40) years, delivery in health facility (AOR = 1.43: 95%CI; 1.29, 1.59) and high community education level (AOR = 1.05: 95%CI; 1.01, 1.17) were positively associated with minimum acceptable diet child feeding practice. Meanwhile, the use of wood (AOR = 0.72: 95%CI; 0.61, 0.86) and animal dug (AOR = 0.34: 95%CI; 0.12, 0.95) as a source of cooking fuel and being from female-headed households (AOR = 0.88: 95%CI; 0.81, 0.96) were negatively associated with minimum acceptable diet feeding practice. Conclusion Child age, mother's educational level, source of cooking fuel, exposure to media, sex of household head, household wealth status, mother working status, age of the mother, place of delivery and community-level education were the significant determinants of minimum acceptable diet feeding practices. Therefore, designing public health interventions targeting higher-risk children such as those from the poorest household and strengthening mothers' education on acceptable child feed practices are recommended.